Pharmacist's Perspectives on Administering a COVID-19 Vaccine in Community Pharmacies in Four Balkan Countries - Turcu-Stiolica, Adina; Kamusheva, Maria; Bogdan, Maria; Tadic, Ivana; Harasani, Klejda; Subtirelu, Mihaela-Simona; Meca, Andreea-Daniela; Šesto, Sofia; Odalović, Marina; Arsić, Jasmina; Stojkov, Svetlana; Terzieva, Emili; et al. (Frontiers in Public Health, 2021)
Community pharmacists expanded their roles and engaged in vaccination services in many countries around the word,but world, but not in Balkan countries. This paper research aimed to assess the perceptions of pharmacists on involvement in COVID-19 vaccine administration in four Balkan countries (Albania, Bulgaria, Romania, and Serbia). A cross-sectional survey was conducted using an online questionnaire that was distributed to community pharmacists from real-world settings across these countries between February and March 2021. A total of 636 community pharmacists were included in the analysis of the survey. The willingness to administer vaccines for COVID-19 (or others well-established in the practice, like a flu vaccine) in the community pharmacies is significantly different among the countries: the pharmacists from Albania were more willing to administer vaccines. The factors associated with the eagerness to vaccinate are almost the same among the countries: the lack of training in the faculty classes and the lack of a special place where to administer the vaccines. Additional significant factors were found in Bulgaria (pharmacists from independent pharmacies wanted more than the pharmacists working in chain pharmacies to administer vaccines) and in Serbia (male pharmacists agreed more with administering the vaccines than the female pharmacists). Further national reforms are needed for adopting the expanding role of the community pharmacists.